2008
DOI: 10.1111/j.1572-0241.2008.02090.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ageing on Small Bowel Video-Capsule Endoscopy Examination

Abstract: Ageing does not affect the completion rate and the quality of bowel preparation for VCE. However, elderly patients have fewer normal studies and more angiodysplasias and tumors in the small bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 15 publications
2
16
1
1
Order By: Relevance
“…Papadopoulos et al investigated 120 consecutive outpatients who underwent VCE for suspected small bowel disease and concluded that: (a) aging did not affect the completion rate and (b) elderly people had more angiodysplasia and tumors than younger patients [11]. On the contrary, Fireman et al, who analyzed 790 subjects retrieved from the Given database, showed that age significantly influenced small bowel transit times [10].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Papadopoulos et al investigated 120 consecutive outpatients who underwent VCE for suspected small bowel disease and concluded that: (a) aging did not affect the completion rate and (b) elderly people had more angiodysplasia and tumors than younger patients [11]. On the contrary, Fireman et al, who analyzed 790 subjects retrieved from the Given database, showed that age significantly influenced small bowel transit times [10].…”
Section: Discussionmentioning
confidence: 97%
“…This could be a bias when analyzing VCE findings (secondary end point of the study). Moreover, two different bowel preparations were used in a nonrandomized way in the two centers which participated in the study [11]. In the latter study, a cut-off of 40 years was used to define the elderly group and the completion rate of VCE studies was not considered [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various results have been reported for the influence of age on CE, but no consensus has been reached [37,38]. However, it is difficult to prescribe laxatives in large quantity to elderly patients due to the risk of adverse reactions, so to avoid losing the merits of ease of use and noninvasive nature of CE, unnecessary preparations should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have suggested that this was true only in western populations and that ulceration was the most common etiology in Asian populations [9, 11, 12]. In this study, 532 patients with OGIB in our hospital from 2006 to 2012 were examined by CE or DBE and the etiologies were retrospectively analyzed.…”
Section: Introductionmentioning
confidence: 99%